John Thorne with Matt Lewis Thorne: Outlaw Cook - Mason, Laura (Petits Propos Culinaires, 1993)
John Thorne with Matt Lewis Thorne: Outlaw Cook: Farrar, Strauss, Giroux, New York 1992: 378 pp, index, bibliography